Improving Your Body Image: Tips for Individuals, Families, and Professionals - Eboni J. Baugh (EDIS, 2006)
FCS2253, a 2-page fact sheet by Eboni J. Baugh, encourages readers to enhance their views of themselves and their bodies and suggests ways that readers can work toward a healthy, balanced body image. Especially relevant for teens. Published by the UF Department of Family Youth and Community Sciences, September 2006.